TIME management by medicinal larvae - Pritchard, David I.; Cerovsky, V.; Nigam, Y.; Pickles, S.F.; Cazander, G.; Nibbering, P.H.; Bultemann, A.; Jung, W. (Wiley, 2015)
Wound bed preparation (WBP) is an integral part of the care programme for chronic wounds. The acronym TIME is used in the context of WBP and describes four barriers to healing in chronic wounds; namely, dead Tissue, Infection and inflammation, Moisture imbalance and a non-migrating Edge. Larval debridement therapy (LDT) stems from observations that larvae of the blowfly Lucilia sericata clean wounds of debris. Subsequent clinical studies have proven debriding efficacy, which is likely to occur as a result of enzymatically active alimentary products released by the insect. The antimicrobial, anti-inflammatory and wound healing activities of LDT have also been investigated, predominantly in a pre-clinical context. This review summarises the findings of investigations into the molecular mechanisms of LDT and places these in context with the clinical concept of WBP and TIME. It is clear from these findings that biotherapy with L. sericata conforms with TIME, through the enzymatic removal of dead tissue and its associated biofilm, coupled with the secretion of defined antimicrobial peptides. This biotherapeutic impact on the wound serves to reduce inflammation, with an associated capacity for an indirect effect on moisture imbalance. Furthermore, larval serine proteinases have the capacity to alter fibroblast behaviour in a manner conducive to the formation of granulation tissue.